Salud mental y derechos humanos: la territorialización de un nuevo saber sobre el terrorismo de Estado y sus efectos - María Soledad Lastra (Nuevo mundo - Mundos Nuevos, 2023)
During the seventies and eighties, from Argentina and on a transnational scale, a territory of knowledge was built around the psychological effects caused by the last military dictatorship. This knowledge was the product of joint ties between psychologists, psychoanalysts and mental health workers who lived through different repressive experiences.This article aims to reconstruct and analyze the initial process of construction and accumulation of specific knowledge about State terrorism in Argentina, from the 1970s to 1985. To do this, it identifies which actors and which groups were formed to attend to the victims and relatives of state repression and what were its main characteristics regarding the work of psychological assistance. This investigation maintains that the work of attention to the victims of State terrorism in Argentina allowed the early delineation of a territory of knowledge about state repression that was linked, from exile and in the country, with the defense of subjugated human rights. This investigation is supported by written documents from human rights organizations and different interviews with the actors of the time.